1994
DOI: 10.1116/1.578864
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced chemical vapor deposition of a-SiC:H films from organosilicon precursors

Abstract: A study of the growth of a-SiC:H films by plasma-enhanced chemical vapor deposition (PECVD) from two organosilicon precursors, silacyclobutane (H2CH2SiCH2CH2 or SCB) and methylsilane (CH3SiH3), is described. A capacitively coupled, parallel plate PECVD system was used to grow films at 250 °C and deposition pressure of 2.0 Torr. Standard (13.56 MHz) and low frequency (0.125 MHz) rf sources were used to generate the deposition plasma. Depositions were performed with and without argon dilution (neat) of the precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 0 publications
0
26
1
Order By: Relevance
“…Density (r), refractive index (n), hardness (H), and elastic modulus (E) of a-SiC:H films produced on c-Si substrates from various organosilicon precursors by different CVD techniques. 800 --33 250 [17] Trimethylsilane (TrMS) Me 3 SiH RHP-CVD 300 2.02 1.74 -- [16] Hexamethyldisilane (HMDS) (Me 3 Si) 2 RHP-CVD 300 1.80 1.84 22 - [12] (Dimethylsilyl)(trimethylsilyl)-methane (DTMSM) Me 2 HSiCH 2 SiMe 3 RHP-CVD 300 1.62 1.88 30 238 [14] Tetrakis(trimethylsilyl)silane (TMSS) (Me 3 Si) 4 Si RHP-CVD 300 -2.09 -- [8,9] Tetramethylsilane (TMS) Me 4 Si P-CVD 400 --18 147 [4] Silacyclobutane (SCB) P-CVD 175 1.71 2.18 18 146 [1,2] Silacyclobutane (SCB) P-CVD 600 2.37 -46 241 [1] Fig. 6.…”
Section: Hardness and Elasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Density (r), refractive index (n), hardness (H), and elastic modulus (E) of a-SiC:H films produced on c-Si substrates from various organosilicon precursors by different CVD techniques. 800 --33 250 [17] Trimethylsilane (TrMS) Me 3 SiH RHP-CVD 300 2.02 1.74 -- [16] Hexamethyldisilane (HMDS) (Me 3 Si) 2 RHP-CVD 300 1.80 1.84 22 - [12] (Dimethylsilyl)(trimethylsilyl)-methane (DTMSM) Me 2 HSiCH 2 SiMe 3 RHP-CVD 300 1.62 1.88 30 238 [14] Tetrakis(trimethylsilyl)silane (TMSS) (Me 3 Si) 4 Si RHP-CVD 300 -2.09 -- [8,9] Tetramethylsilane (TMS) Me 4 Si P-CVD 400 --18 147 [4] Silacyclobutane (SCB) P-CVD 175 1.71 2.18 18 146 [1,2] Silacyclobutane (SCB) P-CVD 600 2.37 -46 241 [1] Fig. 6.…”
Section: Hardness and Elasticitymentioning
confidence: 99%
“…These a-SiC:H thin film coatings can effectively be fabricated from a number of volatile organosilicon precursors by plasma CVD techniques which include conventional (or direct) plasma (P)CVD, [1][2][3][4][5][6] as well as remote hydrogen plasma (RHP)CVD. [7][8][9][10][11][12][13][14] In view of the results of our earlier studies [7][8][9][10][11][12][13][14] the latter technique is particularly beneficial for the formation of high quality aSiC:H films with unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…From a practical standpoint, a lowered dielectric constant prohibits cross-talk and capacitive coupling between parallel circuits. In the case of PECVD a-SiC, most k values found in the literature are 5 or lower [111,126,127], although it has been reported to be as high as 8.7 [120] and 14 [119]. These values appear to depend on the parametric combination of precursor gas chemistry and RF plasma frequency (125-100 kHz in the studies).…”
Section: Feature Articlementioning
confidence: 63%
“…Relatively low hardness values (4 GPa to 7 GPa) were reported for films deposited by high energy ion beam deposition [119]. By comparison, it has been reported that the hardness of a-SiC films deposited by PECVD at 175 °C using silacyclobutane (SiC 3 H 8 ) was ~17.5 GPa [120]. In contrast, films deposited at the same temperature using SiH 4 and methane (CH 4 ) as precursors had hardness values of 10 GPa, which could be increased by up to 25% by annealing [121].…”
Section: Feature Articlementioning
confidence: 95%
See 1 more Smart Citation